Development of an automation system for personnel monitoring and control of ordered products - Gladkov Alexey; Kukartsev Vladislav; Yarkova Anastasia; Kuzmich Roman; Nizameeva Alena (E3S Web of Conferences, 2023)
This paper examines the requirements for the development of an automated system for personnel control, using the example of the operation of a restaurant with its own delivery system. When setting the requirements, various use case diagrams were constructed for different stakeholders working at the selected enterprise. The system to be developed will be useful not only for the employees of the enterprise, as it will eliminate all paperwork, but also for the visitors who purchase services or goods from the selected establishment.